# If f(x) = 2x – 3 and g(x) = 3x – 2, what is f · g?

If f(x) = 2x – 3 and g(x) = 3x – 2, what is f · g?

## This Post Has 7 Comments

1. taniyahreggienae says:

(fg)(x) = f(x)g(x)

=(2x^2-3)*(x+4)

=2x^3 + 8x^2 - 3x - 12

2. keundrecrowe3552 says:

Hello from MrBillDoesMath!

C

Steps:

(2x^2 + 5)(3x^3) =

(2x^2)(3x^3) + 5(3x^3) =

6 x^5            + 15x^3

Which is choice C

Regards, MrB

3. Expert says:

; )

step-by-step explanation: ; )

4. Albertrami2251 says:

In this question, the given functions are

$f(x) = 2x^2 +2 , g(x) =3x+1$

And we have to find the value of

$(f-g)(x)$

Which is equal to

$f(x) - g(x)$

So we have to subtract the two functions that is

$(f-g)(x) = 2x^2 +2 -3x-1 = 2x^2 -3x+1$

Correct option is the second option .

5. 10801652 says:

h(x) = x - 9

Step-by-step explanation:

h(x) = f(x) - g(x)

= - 2x - 6 - ( - 3x + 3) ← distribute parenthesis by - 1

= - 2x - 6 + 3x - 3 ← collect like terms

= x - 9

6. sadsociety41 says:

I think that the answer is A.

7. Expert says:

step-by-step explanation:

idk the answer i want to say 10 but then it would be equal so try 9 but then yeah so yeah we love edgen